Archipelagic ambiguities: the demarcation of modern Japan, 1868-1879 - Jordan B. Walker (Island Studies Journal, 2015)
In the modern era, the demarcation of national boundaries has been a critical feature of the international system. Continent-based demarcations are often more complex than island-based demarcations due, in part, to the former’s generally greater ethnic, religious and historical diversities. However, island-based demarcations, especially when involving archipelagos, can also be a challenging process. States with extensive archipelagos are often faced with geographical archipelagic ambiguities, whereby it is unclear to the archipelagic state and other states where the former’s national boundaries begin and end. This paper explores the archipelagic ambiguities modern Japan was faced with and examines their origins and how they were resolved. By 1868, Japanese leaders realized that Japan’s lingering territorial uncertainties could no longer be left unaddressed if their country was to become a contemporary state. The modern demarcation of Japan was a process lasting more than a decade, until the country resolved the geographical ambiguities along its northern and southern peripheries.